Masked Speech Perception Thresholds in Infants, Children, and Adults. Issue 3 (May 2016) - Leibold, Lori J.; Yarnell Bonino, Angela; Buss, Emily
Abstract : Objective: The primary goal of this study was to compare infants' susceptibility to making produced by a two-talker speech and a speech-shaped noise masker. It is well documented that school-age children experience more difficulty recognizing speech embedded in two-talker speech than spectrally matched noise, a result attributed to immaturity in the ability to segregate target from masker speech, and/or to selectively attend to the target while disregarding the perceptually similar speech masker. However, findings from infant psychophysical studies suggest that infants are susceptible to auditory masking even when target and competing sounds are acoustically distinct. Design: Listeners were infants (8 to10 months), children (8 to 10 years), and adults (18 to 33 years). The task was an observer-based, single-interval disyllabic word detection, in the presence of either a speech-shaped noise or a two-talker masker. The masker played continuously at 55 dB SPL, and the target level was adapted to estimate threshold. Results: As observed previously for closed-set consonant and word identification as well as open-set word and sentence recognition, school-age children experienced relatively more masking than adults in the two-talker than the speech-shaped noise masker. The novel result of this study was that infants' speech detection thresholds were about 24 dB higher than those of adults in both maskers. While response bias differed between listener groups, it did not differ reliably between maskers. Conclusions: It is often assumed that speech perception in a speech masker places greater demands on a listener's ability to segregate and selectively attend to the target than a noise masker. This assumption is based on results showing larger child/adult differences for speech perception in a speech masker composed of a small number of talkers than in spectrally matched noise. The observation that infants experience equal masking for speech and noise maskers suggests that infants experience informational masking in both maskers and raises the possibility that the cues which make the steady noise a relatively ineffective masker for children are learned. Abstract : The present study assessed speech detection thresholds for infants (8-10 months) in the presence of competing two-talker speech or spectrally matched noise. School-age children (8-10 years) and adults (18-26 years) were also tested, using the same method used for testing infants. As expected based on previous studies, the child/adult difference was larger for the two-talker than the noise masker. In contrast, the adult/infant difference was similar across maskers. This result is consistent with the idea that infants have difficulty segregating and selectively attending to target words in both noise and speech maskers.